Investigations on the health status and infection risk of harbour seals (Phoca vitulina) from waters of the Lower Saxon Wadden Sea, Germany - Siebert, Ursula; Lakemeyer, Jan; Runge, Martin; Lienau, Peter; Braune, Silke; Bartelt, Edda; Grilo, Miguel L.; Pund, Ralf (Animals, 2024)
Harbour seals (Phoca vitulina) are the most common pinniped species in the Wadden Sea of Schleswig-Holstein, Hamburg and Lower Saxony, Germany. Their numbers have recovered after significant depletion due to viral outbreaks and effects of anthropogenic activities like pollution and habitat disturbance. Within the Wadden Sea National Park of Lower Saxony the harbour seal is protected. As a top predator in the Wadden Sea ecosystem, the harbour seal is a sentinel species for the state of the environment. Between 2015 and 2017, a total of 80 stranded dead harbour seals were collected along the coastline of Lower Saxony and submitted for pathological investigations. Of these, 70 seals were born in the same year (0–7 months, age group 1) and eight in the previous year (8–19 months, age group 2), due to high mortality rates in these age groups. However, two perennial animals were also available for examination during this period, one of which was in good nutritional condition. Many of the seals that had been mercy-killed and found dead were in poor nutritional status. Histopathological, microbiological, parasitological and virological examinations were conducted on 69 individuals (86% (69/80)) in a suitable state of preservation. Respiratory tract parasitosis, cachexia, and bronchopneumonia were the most common causes of death or disease. Overall, there was no evidence of a relapse of a viral disease outbreak. Macrowaste, such as plastic waste or fishery-related debris, were not found in any gastrointestinal tract of the animals examined. There was also no evidence of grey seal predation. Weakness and cachexia were prominent causes of disease and death in harbour seals found within a few weeks after birth, but bronchopneumonia and septicaemia also developed in slightly older animals. Frequently found microbial pathogens in seals from Lower Saxony were similar to those found in other studies on seals from the Wadden Sea region in Schleswig-Holstein, for example streptococci and Escherichia coli/v. haemolytica, Brucella ...